Mechanical and Thermal Properties of Thermoplastic Random Copolyesters Made from Lipid- Derived Medium and Long Chain Poly (x-hydroxyfatty acid) s - Jose, Jesmy; Li, Shaojun; Bouzidi, Laziz; Leão, Alcides Lopes [UNESP]; Narine, Suresh S. (Wiley-Blackwell, 2014)
The physical properties of novel thermoplastic random copolyesters [-(CH2)(n)-COO-/-(CH2)(n)-COO-](x) made of long (n=12) and medium (n=8) chain length -hydroxyfatty esters [HO-(CH2)(n)-COOCH3] derived from bio-based vegetable oil feedstock are described. Poly(-hydroxy tridecanoate/-hydroxy nonanoate) P(-Me13-/-Me9-) random copolyesters (M-n=11,000-18,500 g/mol) with varying molar ratios were examined by TGA, DSC, DMA and tensile analysis, and WAXD. For the whole range of P(-Me13-/-Me9-) compositions, the WAXD data indicated an orthorhombic polyethylene-like crystal packing. Their melting characteristics, determined by DSC, varied with composition suggesting an isomorphic cocrystallization behavior. TGA of the P(-Me13-/-Me9-)s indicated improved thermal stability determined by their molar compositions. The glass transition temperature, investigated by DMA, was also found to vary with composition. The crystallinities of P(-Me13-/-Me9-)s however, were unaffected by the composition. The stiffness (Young's modulus) of these materials was found to be related to their degrees of crystallinity. (c) 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40492.
Keywords: biopolymers and renewable polymers; copolymers; polyesters; structure-property relations; thermoplastics